APLIKASI SENSOR UGN3505 SEBAGAI PENDETEKSI MEDAN MAGNET - Yulastri Yulastri (Teknik Elektro Politeknik Negeri Padang, 2009)
Sensor UGN3505 using hall effect as magnetic field detection and magnet pole. Proportional value of voltage and magnetic field is accepted by sensor and controlling by microcontroler. This system produces parameter of the magnetic power value which is displayed in LCD (Liquid Crystal Display)